Ayoko ng Plastik exploring the influence of attitudes, norms, and perceived behavioral control on the single-use plastic avoidance behavior of Filipinos - Ferraris, Maria Felicia D.; San Pascual, Ma. Rosel S. (Quezon City University of the Philippines Diliman, 2025)
The overconsumption of single-use plastic (SUP) in the Philippines has resulted in a plastic pollution crisis leading to frequent flooding, risks to human health, and threats to marine biodiversity. In response, Filipinos adapted single-use plastic avoidance behavior (SPAB), such as the use of ecobags, to minimize their SUP consumption.

This study examines how attitudes, norms, and perceived behavioral control shape SPAB of Filipinos residing in Metro Manila. Anchored on Ajzen’s (1991) Theory of Planned Behavior, the study conducted in-depth interviews with Filipinos practicing SPAB to surface how these factors shape their behavior.
The findings reveal that while there is growing awareness and concern about plastic pollution, SPAB remains influenced by competing priorities, socio-economic limitations, and structural barriers. Positive attitudes toward the environment are not always enough to translate into action, especially when sustainable alternatives are inaccessible or inconvenient. Social influences from peers and family, as well as policies such as the ban on plastic, play critical roles in promoting SPAB, although their effectiveness varies. Furthermore, the study highlights that ingrained habits and time constraints significantly impact individuals’ ability to adopt consistent SPAB.
Thesis
Keywords: Plastic scrap -- Environmental aspects -- Philippines; Environmental protection -- Citizen participation -- Philippines; Consumer behavior -- Environmental aspects -- Philippines